Administrative communication systems and their role in crisis management A field study on workers at Damascus University - Central Administration: A field study on workers at Damascus University - Central Administration (Journal of Hama University, 2024)
The aim of the research is to identify the role of administrative communication systems in crisis management at the University of Damascus - the central administration, and to identify the differences between the opinions of the research sample about crisis management according to the variable (gender, academic qualification). (110) employees and (105) were recovered, and the statistical program (SPSS) was used to reach the results, which showed that the reality of administrative communication was high and the reality of crisis management was average in Damascus University - Central Administration. And that there is a statistically significant effect of administrative communication systems in crisis management, and there are no statistically significant differences between the members of the research sample regarding crisis management according to the demographic variables (gender, academic qualification). The research recommended the need to work on developing organizational structures that modernize administrative communication systems by proceeding with the networking project and strengthening the decision support system, which will have repercussions on the development of administrative communications. It also stressed the establishment of a special unit for crisis management that works to facilitate tasks and coordination..
Keywords: administrative communication, crisis management, Damascus University, central administration.